System analysis of the secondary condensation unit in the context of improving energy efficiency of ammonia production - Babichenko, Anatoliy; Velma, Vladimir; Babichenko, Juliya; Kravchenko, Yana; Krasnikov, Igor (Eastern-European Journal of Enterprise Technologies, 2017)
We established the mismatch between real and design coefficients of heat transfer, which is predetermined by the underestimation of condensation thermal resistance. The processes of heat exchange in a condensation column are identified and the equations for determining the coefficients of heat exchange, heat transfer and the concentration of ammonia in the circulation gas at the outlet of the column are derived. By applying the method of mathematical modeling, we defined necessary conditions for temperature distribution to exclude from the circuit of the unit for synthesis a turbo-compressor refrigeration unit with electric drive of capacity up to 4000 kW·h and reduction in the cooling temperature of circulation gas from 0 °C to – 5 °C at maximum thermal load with circulation gas on the complex of secondary condensation. The hardware-technological design is developed for the stage of secondary condensation based only on the absorption and steam-ejector refrigeration systems that utilize the heat of material flows of low (above 100 °C) and super-low (to 90 °C) potentials. We defined efficiency indicators for the reduction of specific energy consumption by electricity and natural gas, which are 60 kW·h/t NH3 and 1.2 m3/t NH3.